Digging into Canadian Soils An Introduction to Soil Science - Krzic, Maja; Walley, Fran; Diochon, Amanda (Open textbook library., 2021)
Written entirely by members of the Canadian Society of Soil Science, "Digging into Canadian Soils: An Introduction to Soil Science" provides an introduction to the core disciplines of soil science, and introduces the concepts and vocabulary needed by students just beginning their soil science journey. The textbook provides supplementary materials that are specific to regions in Canada, or may be of specific interest beyond what might be considered introductory soil science material. Importantly, the textbook also is intended to introduce students to the Canadian System of Soil Classification by providing examples from across the length and breadth of the world’s second largest country, and to the Canadian Society of Soil Science, whose members share a common passion for soil science and are keen to share and instill this passion with students across Canada.